The Political Economy of Lithuania’s Public Finance - Gylys, Povilas (Ekonomika, 2003)
Traditionally Lithuania’s public finances are discussed in terms of tax burden and tax administration. Such issues as composition of tax revenues or the structure of public expenditure for some reasons are less atractive both for economists, journalists, politicians and general public at large. The purpose of this article is to fill this gap doing it in the political, cognitive and ideological context existing in our country. The subject is explored in the framework of methodological holism.